A systematic review of transfer studies in third language acquisition. (January 2020) - Puig-Mayenco, Eloi; González Alonso, Jorge; Rothman, Jason
The present systematic review examines what factors determine when, how and to what extent previous linguistic experience (from the first language, second language or both languages) affects the initial stages and beyond of adult third language (L3) acquisition. In doing so, we address what a bird's eye view of the data tells us regarding competing theoretical accounts of L3 morphosyntactic transfer. Data couple together to suggest that some factors are more influential than others. As discussed, the systematic review transcends the field of adult multilingualism precisely because of what it reveals, as a prima facie example in behavioral research, in terms of how different types of methodological considerations impact the way data are interpreted to support or not particular claims.